Catalytic ignition, quenching and burning of acetone in air on platinum wires of different diameters - Chernenko, Oleksander; Kalinchak, Valery; Kopiyka, Oleksander; Fedorenko, Anna; Roziznanyi, Mykhaylo (Physics and Chemistry of Solid State, 2025)
The relationship I/d based on the analysis of the analytical dependence of the stationary temperature of the catalyst thread on the heating current strength is proposed in the work. It allows estimating the range of current strength for a certain diameter of the catalyst thread, within which observation of ignition and extinction of the heterogeneous catalytic reaction is possible. Experimental studies for the catalytic oxidation of acetone in air on a platinum catalyst thread with diameters of 20, 70, and 95 microns showed that considering convection requires adjusting this relationship as I/d•Nu^1/2. As a result, the representation of the temperature of the catalyst thread from this complex exhibits coordination of low- and high-temperature oxidation regimes, as well as critical conditions of catalytic ignition and extinction. This assessment is possible when using an electrical heating circuit of the thread in the current stabilization mode.